The quest for a philosophical YHWH (part 1) : Old Testament studies and philosophy of religion - Gericke, Jaco (Old Testament essays, 2005)
In Old Testament studies, philosophy of religion is seldom if ever utilised in research on ancient Israelite religion. No independent and officially recognised interpretative approach currently exists that allows biblical scholars to concern themselves solely with a philosophical analysis of the religious beliefs of ancient Yahwism(s). In this article, the first in a series of three, the author acknowledges this gap in the research and seeks to pioneer the utilisation of 'philosophy of religion' as an auxiliary discipline in biblical interpretation. Following in-depth discussions on related historical, meta-philosophical, heuristic and hermeneutical issues, the author proposes the establishment of a new approach to the text called 'philosophicalcritical analysis'. This will at last make it possible for biblical scholars to engage in philosophy of religion both on the level of exegesis (via 'philosophical criticism') and on a larger scale (via 'philosophy of Old Testament religion').